Hubungan Sosial Ekonomi Terhadap Status Gizi Remaja Putri di SMA Negeri 11 Kota Jambi - Filius Chandra; Aisah Aisah (Jurnal Akademika Baiturrahim Jambi, 2023)
Adolescents are individuals both women and men who are between students and adults. The limit for adolescents in this case is the age of 10-19 years according to the classification of the World Health Organization (WHO). The nutritional needs for adolescents are very large because they are still growing. Adolescents need energy/calories, protein, calcium, iron, zinc and vitamins to fulfill physical activities such as school activities and daily activities. Nutritional problems are generally caused by economic problems, lack of food, poor environmental quality. Based on the initial survey conducted on students of SMA Negeri 11 Jambi City, which was conducted by interview, there were 8 out of 11 students who did not understand the nutritional status of adolescents.the number of samples in this study were 79 respondents. To find out the size of the problem with the dependent variable and related factors, where the measurement of the variable is momentary and only once.After the data was obtained from the results of filling out the questionnaire by the respondents, it was processed using computer facilities and then analyzed into two forms of analysis, namely univariate analysis and bivariate analysis.The majority of respondents with normal nutritional status, namely 25 people (41.0%) came from families with high incomes and the majority of respondents with thin nutritional status had low family income, namely 22 people (36.1%). From the bivariate analysis of the relationship between family income and nutritional status (BMI/U), a p value = 0.000 (<0.05) is obtained, which means that there is a significant relationship between family income and nutritional status based on the BMI/U index at SMA Negeri 11 Kota Jambi.